Kepemimpinan Pembelajaran Guru Penggerak Dalam Program Merdeka Belajar - Binti Masruroh; Nur Kolis (Excelencia: Journal of Islamic Education & Management, 2024)
The Ministry of Education's policy of Merdeka Belajar Guru Penggerak as a manifestation of the government's efforts to improve the quality of learning which is oriented towards improving the process and learning outcomes of students, so the strategic step taken is to provide education and training for teachers in the form of professional development through training and mentoring that focuses on learning leadership in the transformation of the educational ecosystem to realize the profile of Pancasila students. The initial condition of understanding of teachers in Garuda Kindergarten and Tunas Bangsa PKK Kindergarten does not understand the meaning and competence of learning leaders which is the focus of training and mentoring organized by the Ministry of Education and teachers do not fully understand the meaning of independent learning and the use of the environment and so far training for teachers has been centralized on the role of supervisors so that the meaning of independent learning is still very limited. The objectives of this study are: 1) to find out the characteristics of the learning leadership of the driving teacher in the independent learning program, 2) to find out the competence of the driving teacher and 3) to see the impact of the driving teacher's learning leadership for Garuda Kindergarten and PKK Tunas Bangsa Kindergarten. The method used in this research is a qualitative method with a multisite study research type. Data collection was done through interviews, observation, and documentation. While data analysis techniques through data collection, data condensation, data presentation, and conclusion making. The results of the study show: 1) The learning leadership of the lead teacher in Garuda Kindergarten and Tunas Bangsa PKK Kindergarten has the ability to set goals, utilize strategic resources, be able to assist in planning and evaluating teaching, promote the education unit and participate in learning and teacher development and ensure an environment that supports teacher development, 2) the lead teacher in Garuda Kindergarten and Tunas Bangsa PKK Kindergarten mastered the core competencies of the lead teacher program direction, namely developing self and others, leading learning, leading school management, and leading school development, 3) the learning leadership of the lead teacher in Garuda Kindergarten and Tunas Bangsa PKK Kindergarten has a good impact on the implementation of the independent learning independent play curriculum in accordance with the objectives of early childhood education.